Inflation and Financing of Commercial Insurance in the Field of Treatment - Moslem Sharif; Rouzbeh Hojabri; Jalal Saidpour; Hamed Rahimpour Langroudi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: In inflationary conditions, financing is one of the most important and challenging issues in different sectors of economy, including health. Health financing means the way money is collected, accumulated and spent for health care services. The process undergoes a change in inflationary conditions. Methods: This is a qualitative research. The data were collected through a survey of documentation related to health system expenditures in Iran.. The search strategy in this study was based on the PRISMA protocol. In the preliminary search, 147 official documents and reports were obtained. After removing inconsistent and repetitive cases, 47 documents were examined. These documents were classified into 11 categories and the position analysis was based on this. Results: Findings show that inflation has had a very negative impact on Iran's financing system; specifically inflation has seriously threatened country's health insurance industry. The study of trend of return loss index in Commercial Insurance in The field of treatment revealed its unfavorable status in the study years. However, the demand for these insurance packages has also been increasing. Conclusion: The rising trend of inflation in the field of treatment in the study duration, along with increased focus of quality services in private sector, in contrast to the public sector, have led to the transfer of treatment costs from public to private sector. This has increased the share of payment from the pocket of patients. This process has increased the influence of this sector in determining tariffs. The lack of authority of insurance companies to monitor and evaluate the performance of these centers is considered as an important factor in transfer of health finances from state and social insurance to private sector and commercial insurance. It should be noted that during the period under study in health market of Iran, the inflation rate and the amount of direct payments have been interacting, and each has intensified another.